Dynamic Modelling And Analysis Of 3D Overhead Gantry Crane System - Ab Hadi, Nik Azran; Mohd Annuar , Khalil Azha; Harun , Mohamad Haniff; Mohd Ab. Halim, Mohd Firdaus; Mirin, Siti Nur Suhaila; Azahar, Arman Hadi (Science Publishing Corporation, 2018)

(untitled)
The overhead gantry crane systems are extensively used in harbours and factories for transportation of heavy loads. The crane speeding up,required for motion,always induces undesirable load swing.This writings present dynamic modelling of a 3D overhead gantry crane system based on closed-form equations of motion.By using the Lagrange technique,a 3D overhead gantry crane system nonlinear dynamic model is deriving.Then perform a linearization process to obtain a linear model dynamic system.Finally, simulation results systems responses of the derived nonlinear and linear model are presented showing the accuracy and performance of both model.